2004
DOI: 10.1089/1545457041526290
|View full text |Cite
|
Sign up to set email alerts
|

Use of siRNAs and Antisense Oligonucleotides Against Survivin RNA to Inhibit Steps Leading to Tumor Angiogenesis

Abstract: The antiapoptotic protein survivin is an attractive target in cancer therapy because it is expressed differently in tumors and normal tissues and it is potentially required for cancer cells to remain viable. Given that survivin is also overexpressed in endothelial cells (ECs) of newly formed blood vessels found in tumors, its RNA targeting might compromise EC viability and interfere with tumor angiogenesis. We used two antisense strategies against survivin expression, antisense oligonucleotides (aODN) and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…No significant changes in proliferation were observed, suggesting Survivin ⌬Ex3 does not play a significant role in regulating cell growth ( Figure 4C). Treatment of HUVE cells with a combination of shRNAs that target all Survivin splice variants, with the exception of Survivin 2␣, resulted in a statistically significant increase in apoptosis (mean ϭ 32.5%), as has been previously demonstrated 26 ( Figure 4A). …”
Section: Org Fromsupporting
confidence: 82%
See 3 more Smart Citations
“…No significant changes in proliferation were observed, suggesting Survivin ⌬Ex3 does not play a significant role in regulating cell growth ( Figure 4C). Treatment of HUVE cells with a combination of shRNAs that target all Survivin splice variants, with the exception of Survivin 2␣, resulted in a statistically significant increase in apoptosis (mean ϭ 32.5%), as has been previously demonstrated 26 ( Figure 4A). …”
Section: Org Fromsupporting
confidence: 82%
“…Studies of the Survivin splice variants have been performed almost exclusively with cancer cells; however, Survivin itself has been increasingly implicated in other physiologic and pathophysiologic processes, including angiogenesis. [22][23][24][25][26] Previous studies have shown that the main isoform of Survivin is expressed at higher levels in the endothelial cells of newly formed blood vessels within tumors 33 as well as within injured or ischemic brain. 34 Functional studies have not yet addressed the roles of the individual splice variants in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survivin may also promote the proliferation of endothelial cells, and silencing survivin may be able to inhibit the expression of VEGF (25). The import of survivin-targeting antisense oligonucleotides into cultured endothelial cells may promote the apoptosis of these endothelial cells and inhibit angiogenesis (26,27). A previous study has demonstrated that basic fibroblast growth factor and survivin also produce synergistic effects, with positively associated expression patterns in lung cancer and OSCC (23).…”
Section: Discussionmentioning
confidence: 99%